MODEL PEMBELAJARAN BAHASA ARAB BERBASIS KOMUNIKATIF DALAM MENINGKATKAN KEMAMPUAN KETERAMPILAN BERBICARA SANTRI (STUDI KASUS DI MADRASAH DINIYAH AL-KHOIROT MALANG) - Ulum, Fahmi; Zainuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigates the instructional framework applied to boost the Arabic speaking skills of students at Madrasah Diniyah Al-Khoirot, Malang. Employing a qualitative case study design, this exploration examines how the textbook Modern Arabic for Beginners: Conversation, Reading, and Writing is utilized pedagogically. The classroom activities comprise group reading, semantic explanations, direct translation, and practical conversational exercises based on the topics. Interestingly, teachers place greater emphasis on fluency and psychological assurance rather than grammatical precision, avoiding instant corrections of i'rab errors. Furthermore, vocabulary acquisition is supported by tasks involving writing and memorizing key mufradat, reinforced by systematic daily, weekly, and monthly murajaah (reviews). The outcomes reveal that despite students achieving good comprehension in reading and vocabulary retention, their understanding of i'rab rules is still restricted. On the other hand, a substantial growth in speaking self-confidence is observed, which translates into active communication during classes and everyday socializing within the Islamic boarding school community. Keywords: Arabic Language Instruction, Communicative Approach, Speaking Proficiency, Mufradat, Madrasah Diniyah Al-Khoirot Malang.